Review the leafhopper genera Parafagocyba Kuoh et Hu and Zorka Dworakowska (Hemiptera: Cicadellidae) with description of a new species and two new records from China - Huang, Min; Zhang, Yalin (Zootaxa, 2013)
The leafhopper genus Parafagocyba Kuoh et Hu, 1992 and Zorka Dworakowska, 1970 are reviewed. One new species of Parafagocyba is described and illustrated, Parafagocyba forficula n. sp., and Parafagocyba multimaculata Kuoh et Hu 1992 is transferred to the genus of Zorka Dworakowska, 1970. Two species of Zorka are also newly recorded from China.